Does School Lunch Fill the "SNAP Gap" at the End of the Month?. (15th May 2019) - Laurito, Agustina; Schwartz, Amy Ellen
Abstract : This article investigates the relationship between the timing of Supplemental Nutrition Assistance Program (SNAP) benefit payments and participation in school lunch and breakfast using the National Household Food Acquisition and Purchase Survey. An event study approach examines participation over the five‐day window before and after the SNAP payment. We find that school lunch participation decreases by 17–23 percentage points immediately after the SNAP payment among 11–18 year olds while breakfast drops by 19–36 percentage points. The decline begins the day prior to payment. We find no effects for 5–10 year olds. Models examining participation over the full SNAP month using individual fixed effects yield similar findings. Among teenagers, participation in school lunch and breakfast decline in the first two weeks of the SNAP month, increasing afterward. Non‐school meals show the opposite pattern. Overall, results indicate SNAP households rely more on school lunch and breakfast toward the end of the SNAP month.